The impact of gambling advertising on gambling severity: a path analysis of factors of psychological distress in individuals with gambling disorder - Lopez-Gonzalez, Hibai; Granero, Roser; Fernández-Aranda, Fernando; Griffiths, Mark D.; Jiménez-Murcia, Susana (Frontiers in Psychology, 2025)
BackgroundThere is a consensus in the literature that gambling advertising disproportionately affects those experiencing higher gambling severity. However, the relationship of gambling advertising and severity is typically assessed among samples recruited from online panels using screening tools as the method to categorize the gambling severity status of participants. Alternatively, other studies use small groups of gamblers (i.e., qualitative studies). The present paper reports findings from a sample of gamblers diagnosed with gambling disorder by professional clinicians via individual interviews. The study investigated the association between gambling advertising and gambling severity by looking at other psychologically relevant variables such as impulsivity, emotion regulation, and general psychopathology.MethodsA sample of 210 consecutive treatment-seeking patients was recruited from a public hospital from June 2019 to January 2021. A path analysis model was run to determine the relationship between the variables. Gambling advertising was constructed as a latent variable, comprising the perceived impact of gambling advertising, persuasion knowledge, and the attitudes towards gambling advertising.ResultsGamblers with greater gambling severity reported higher perceived impact of gambling advertising, and more positive attitudes toward gambling advertising. Gambling advertising was a mediator in the paths between emotion regulation and gambling severity, and between impulsivity and gambling severity.ConclusionThe study demonstrates among individuals with verified gambling disorder that there is a relationship between gambling advertising and gambling severity. Regulators have an empirical basis on which to restrict the exposure to gambling advertising of vulnerable groups.